Difficult Asthma - Heaney, Liam G.; Menzies-Gow, Andrew (Clinical Focus Series, 2013)
Most patients with asthma are easily diagnosed and treated with the use of an inhaler or medication. Approximately five per cent of people that suffer from asthma have difficult or refractory asthma, whereby they experience persistent problems that are not controlled by standard treatment methods. Part of the Clinical Focus Series, this book provides a complete overview of difficult asthma, discussing the clinical assessment and management of this complex condition. Beginning with the epidemiology and characteristics of severe asthma, the book defines current understanding of the immunological mechanisms and disease heterogeneity. It also offers insight into how the condition can affect the physical and psychological aspects of a person s life. Separate chapters examine novel therapeutic strategies and the economic burden of refractory asthma.